Determination of Fractal Area of the Koch Snowflake - Kamil, Abdul; Hidayat, Rusli; Purnomo, Kosala Dwidja (Majalah Ilmiah Matematika dan Statistika, 2017)
The Koch Snowflake Island (Koch Snowflake) is composed of three Koch curves rotated by suitable angles and fitted together. The Koch curve is constructed using an iterative procedure beginning with the initiator of the set as the unit line segment. The unit line segment is divided into thirds and the middle third removed, then replaced with equilateral triangle without base. In this article to get formulation of the area fractals Koch Snowflake and its variations, generated by generator equilateral triangle, isosceles triangle and square to the sides of the regular polygon which has n sides.